Comparative public policy - Dodds, Anneliese (Houndmills, Basingstoke, Hampshire Palgrave Macmillan, 2013)
"A major new introduction to the comparative study of public policy. It examines the policy process in a wide range of policy areas and countries and considers the challenges of transferring policies from one society to another."--Publisher's website.
Introduction -- Why Compare Public Policies? -- Differences between Public Policies: An Introduction -- Economic Policy -- Welfare Policy -- Health Policy -- Education Policy -- Environmental Policy -- Interests and Public Policy -- Ideas and Public Policy -- The Impact of Institutions on Public Policies -- Policy Transfer -- Policy-making Beyond the Nation State -- Comparative Public Policy - Excluding the Majority World? -- Doing Comparative Public Policy -- Conclusion.
Includes bibliographical references and index.
Keywords: Comparative government; Policy sciences